Assessing the impact of eco-innovations through sustainability indicators: the case of the commercial tea plantation industry in Sri Lanka - A. D. Nuwan Gunarathne; H. M. P. Peiris (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2017)
Innovative processes aimed at sustainable development or eco-innovations have received increasing attention during the past years despite the lack of theoretical and methodological approaches to analyzing their impact. This paper focuses on how sustainability indicators can be used to measure the effects of "non-technical" eco-innovations in the Sri Lankan tea plantation sector. After carrying out an experimental case study on a commercial tea plantation, we employed a combination of physical and monetary sustainability indicators to evaluate the initial results of the eco-innovation. It shows that innovations aimed at improving economic benefits often result in unintentional environmental and social benefits that support a lean-green relationship. It reveals the difficulty in having a standardized set of indicators to measure the impact of eco-innovations owing to the multidimensionality of sustainability. Hence, the case study suggests adopting broad sustainability indicators that represent the wholeness of the system while capturing the long-term impact.
Keywords: 650; Agriculture; Eco-innovation; Sri Lanka; Sustainability; Sustainability accounting; Sustainability indicators; Tea industry; Triple bottom line